Prisoner-warder ratio parity in a South African Correctional Centre: Repercussions on prison work environment and correctional security personnel - Magungxu, Vuyokazi; ., Philani Moyo (Journal of Economics and Behavioral Studies, 2014)
South Africa has one of the highest inmate populations in the world. In order for the South African Correctional Services system to provide an environment conducive for the appropriate rehabilitation and reformation of its many inmates, it requires a balanced prisoner-warder ratio based on international standards. But is this the case in South African prisons? This is one of the questions that this article engages as it examines the prisoner-warder ratio at the East London Maximum Correctional Centre (ELMCC) in an effort to understand the effects of prison overcrowding on the prison work environment and correctional personnel. Based on empirical evidence gathered through qualitative techniques, the study finds a disproportionate prisoner-warder ratio at the ELMCC. This disproportion has a number of negative effects on the prison work environment and direct security personnel on duty. For example, high absenteeism is rife with warders frequently on sick leave while others are regularly on temporary incapacity leave. High stress levels are also a major problem pushing many warders into alcohol abuse. Cognitive job satisfaction and organizational commitment are also negatively affected by this disproportion with the majority of warders indicating poor work performance due to low morale and lack of motivation.